Optimización del consumo energético de pozos con sistema de levantamiento artificial PCP y ESP de la troncal siete de campo rubiales mediante simulación (2019)
Taking into account the existence of critical wells due to problems related to the performance of ALS due to their high energy consumption, in Rubiales Field, specifically in Trunk 7, resizing tubings and/or redesigning Artificial Lift Systems are proposed to reduce this demand. Therefore, the most critical wells were identified and selected considering the variables of production, efficiency and energy consumption. The field's information was analyzed to determine how many wells perform as optimization opportunities, primarily considering the Lutz Index and other decision factors. Once the optimization potential has been identified, its technical evaluation is carried out and with the identification of viable technical alternatives, an economic evaluation was carried out through the BreakEven model of the field, taking the NPV and PayBack as indicators of value.